Characterizing Neural Entrainment to Hierarchical Linguistic Units using Electroencephalography (EEG) - Ding, Nai; Melloni, Lucia; Yang, Aotian; Wang, Yu; Zhang, Wen; Poeppel, David (Frontiers in Human Neuroscience, 2017)
To understand speech, listeners have to combine the words they hear into phrases and sentences. Recent magnetoencephalography (MEG) and electrocorticography (ECoG) studies show that cortical activity is concurrently entrained/synchronized to the rhythms of multiple levels of linguistic units including words, phrases, and sentences. Here we investigate whether this phenomenon can be observed using electroencephalography (EEG), a technique that is more widely available than MEG and ECoG. We show that the EEG responses concurrently track the rhythms of hierarchical linguistic units such as syllables/words, phrases, and sentences. The strength of the sentential-rate response correlates with how well each subject can detect random words embedded in a sequence of sentences. In contrast, only a syllabic-rate response is observed for an unintelligible control stimulus. In sum, spatial-temporal neural activity recorded by EEG provides a useful measure to characterize neural encoding of hierarchical linguistic units, potentially even in individual participants.